1952
DOI: 10.1136/jcp.5.4.366
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Dextran Sulphate as a Blood Anticoagulant in Biological Research

Abstract: Several well-known anticoagulants are in use for blood sample tubes, each having some special application, but there is little doubt that the naturally occurring anticoagulant, heparin, would find wider application were it not so difficult to prepare and consequently expensive. Chemically prepared sulphuric esters of polysaccharides are known to have anticoagulant action. One of these, dextran sulphate, has recently been prepared (Ricketts, 1952) in a form suitable for therapeutic use (Walton, 1951 In the fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Dextran derivatives, including DS, have been reported to be useful in the treatment of hemorrhages, burns, and surgery, with antiviral, anticoagulant, and adjuvant properties. [28][29][30][31] It also improves blood flow and prevents erythrocyte aggregation, lowering the risk of thrombosis and postoperative pulmonary emboli. 32 CMC is polysaccharide with excellent bioadhesive properties, biodegradability, and biocompatibility.…”
Section: Resultsmentioning
confidence: 99%
“…Dextran derivatives, including DS, have been reported to be useful in the treatment of hemorrhages, burns, and surgery, with antiviral, anticoagulant, and adjuvant properties. [28][29][30][31] It also improves blood flow and prevents erythrocyte aggregation, lowering the risk of thrombosis and postoperative pulmonary emboli. 32 CMC is polysaccharide with excellent bioadhesive properties, biodegradability, and biocompatibility.…”
Section: Resultsmentioning
confidence: 99%
“…Dextran sulfate was used historically in medicine as an anticoagulant [18], but has found other uses, such as an antiviral agent shown to inhibit binding of HIV-1 to CD+ T-lympohocytes [19]. Furthermore, studies with PPy:DS composite polymers have demonstrated the material supports the adhesion of PC12 [20] and skeletal muscle [9] myoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…The anticoagulant effect of DS has been described for a long time [33], but has not been used in antitumor therapy. However, this effect might be useful in intracavitary chemotherapy of serous cavity tumors.…”
Section: Introductionmentioning
confidence: 99%